2004
DOI: 10.1007/s00430-003-0190-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathology of inflammatory cardiomyopathy

Abstract: Endomyocardial biopsy (EMB) is often performed in patients presenting with sudden onset of heart failure to identify myocarditis. The introduction of immunohistochemical techniques for the detection and differentiation of infiltrating immune cells, specific adhesion molecules and MHC class I and II molecules increased the prognostic value of EMB in the diagnosis of myocarditis considerably. A major breakthrough in the understanding of pathogenetic mechanisms in myocarditis was achieved by diagnostic use of mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
15

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 42 publications
3
93
0
15
Order By: Relevance
“…However, in common with others [19,23] we also noted that the Dako antiserum can, under certain conditions, label tissues in which vp1 production is not expected. In particular, our preliminary work revealed that, when applied to formalin-fixed, paraffin-embedded sections of Coxsackie-infected neonatal mouse organs, this antibody stained some tissues which were reported to be negative for viral RNA by in situ hybridisation [24].…”
Section: Discussionsupporting
confidence: 89%
“…However, in common with others [19,23] we also noted that the Dako antiserum can, under certain conditions, label tissues in which vp1 production is not expected. In particular, our preliminary work revealed that, when applied to formalin-fixed, paraffin-embedded sections of Coxsackie-infected neonatal mouse organs, this antibody stained some tissues which were reported to be negative for viral RNA by in situ hybridisation [24].…”
Section: Discussionsupporting
confidence: 89%
“…6 Endothelial cells have been recognized as targets for PVB19 infection in small cardiac vessels, whereas cardiomyocytes have so far not been described as targets for this virus type. 9,23,24 The most likely cardiac location of PVB19 in our patient is the endothelium, based on all currently available studies in humans. 9,23,24 Alternatively, PVB19 could also reside in other cardiac cell types or in blood-borne cells, which previously might have migrated into the heart.…”
Section: Pvb19 As a Cardiac Pathogenic Agentmentioning
confidence: 97%
“…9,23,24 The most likely cardiac location of PVB19 in our patient is the endothelium, based on all currently available studies in humans. 9,23,24 Alternatively, PVB19 could also reside in other cardiac cell types or in blood-borne cells, which previously might have migrated into the heart. However, at the time of investigation, no circulating cells carrying PVB19 were detected in any patient.…”
Section: Pvb19 As a Cardiac Pathogenic Agentmentioning
confidence: 97%
“…The relevance of the CD8 + T cells for an efficient elimination of CVB3 during the acute phase of myocarditis was demonstrated in the mouse model of enterovirus myocarditis (Klingel et al, 2003). Moreover, the severity of CVB3 myocarditis was found to be magnified in CD8 2/2 mice (Opavsky et al, 1999), suggesting a dominant role of CD8 + T cells in the protection against enterovirus challenge.…”
Section: Introductionmentioning
confidence: 99%